Unitarian Universalist Church of Fresno's Men's Group Snow Outing at Murphy's Cabin - Watkins, Howard::::::::: (1986)
On skis and ready to move out: Tom Richardson, Sam Zutler, Bill Murphy, Armin Biberthaler, Saul Eskin and Howard Watkins